Processos identitários e saúde reprodutiva: estudos com um grupo de doulas - Duarte, Camila Nogueira Bonfim (2016)
Given the importance of the support offered to women by doulas and their increasing role in birth support around the world and in Brazil, this dissertation reports a research which aimed to investigate identity processes of a doula group and adopted Social Identity Theory. To this end two studies were conducted with a group of five doulas, referred to as “Bem Nascer”, active in a city of the state of Espirito Santo. They agreed voluntarily to participate in this research. The two studies are presented in article format to best present the results and structured the discussions. The first article presents the results obtained through participant observation of ten workshops about pregnancy and childbirth, promoted by the group “Bem Nascer” with pregnant women. We collected field notes and analyzed the data with the hermeneutic-dialectic method. We identified 3 categories: 1) Descriptions of the workshops; 2) In-group interactions scenes; 3) Out-group interactions scenes. We observed that the doulas, when interacting with the pregnant women, performed roles such as: friends, instructors, professionals, feminist activists, and that they attributed positive characteristics to “pro-humanized birth men” and to “humanized physicians” in contrast to “traditional men” and to “technocratic physicians”. We inferred that such attribution of value occurs on the basis of crossed categorization. We verified that the practices of the doulas in the field of reproductive health were suitable to the guidelines of the Brazilian public health system and that they disseminated feminist ideals to middleclass women. For the second article, we administered semi-structured interviews with five doulas. We identified 134 themes and 6 categories in the interviews through thematic content analysis. The doulas construct their identity based on feminist activism, the humanization of birth movement and their own work group, which provides trust-based relationships, professional network and friendship. The doulas held negative attitudes towards most physicians, with the exception of those perceived to be humanized. We discuss that the investigated doulas adopted feminism to construct identity processes and that their activism, their work group and their regular encounters with pregnant women are strategies of social change, which contribute to transform health practices and gender relations.